Why Human Enhancement is Necessary for Successful Human Deep-space Missions. Issue 4 (2nd October 2019) - Szocik, Konrad; Braddock, Martin
Abstract : While humans have made enormous progress in the exploration and exploitation of Earth, exploration of outer space remains beyond current human capabilities. The principal challenges lie in current space technology and engineering which includes the protection of astronauts from the hazards of working and living in the space environment. These challenges may lead to a paradoxical situation where progress in space technology and the ability to ensure acceptable risk/benefit for human space exploration becomes dissociated and the rate of scientific discovery declines. In this paper, we discuss the predominant challenges of the space environment for human health and argue that development and deployment of a human enhancement policy, initially confined to astronauts – for the purpose of future human space programmes is a rational solution to these challenges.